2020
DOI: 10.3389/fnins.2019.01389
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gait Treatment With a Single-Leg Hybrid Assistive Limb System After Acute Stroke: A Non-randomized Clinical Trial

Abstract: We hypothesized that a single-leg version of the Hybrid Assistive Limb (HAL) system could improve the gait and physical function of patients with hemiparesis following a stroke. In this pilot study, we therefore compared the efficacy of HAL-based gait training with that of conventional gait training (CGT) in patients with acute stroke. Patients admitted to the participating university hospital were assigned to the HAL group, whereas those admitted to outside teaching hospitals under the same rehabilitation pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 44 publications
0
24
0
Order By: Relevance
“…Several studies on HAL treatment use different evaluation parameters, such as improvement of independent walking for acute stroke, improvement of activities of daily living for subacute stroke, improvement of spatiotemporal gait parameters for chronic stroke, improvement of health-related quality of life for chronic spinal cord injury, and a decrease of spasticity for chronic spinal cord injury 17,18,[26][27][28] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies on HAL treatment use different evaluation parameters, such as improvement of independent walking for acute stroke, improvement of activities of daily living for subacute stroke, improvement of spatiotemporal gait parameters for chronic stroke, improvement of health-related quality of life for chronic spinal cord injury, and a decrease of spasticity for chronic spinal cord injury 17,18,[26][27][28] .…”
Section: Discussionmentioning
confidence: 99%
“…2 and 3). It is presumed that these are the results of appropriate walking support by cybernetic control and securing of repeated walking amount 18,[38][39][40] . Although many clinical studies have been conducted in the last decade, more clinical studies, particularly high-quality design studies, are needed to elucidate the mechanism of HAL treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of our previous non-randomized clinical trial suggested that the HAL treatment group showed a significant improvement in FAC after nine sessions compared with the conventional treatment group (Watanabe et al, 2020). Furthermore, examination of changes in FAC on a weekly basis revealed a significant group × time point interaction in FAC of the HAL treatment group, suggesting that independent walking may be improved at an early stage [unpublished data].…”
Section: Introductionmentioning
confidence: 99%
“…To date, several types of HAL (HAL for lower limbs and HAL for single joints) have been applied for several musculoskeletal and neurological disorders [ 10 – 14 ]. It has been reported that the lower limb type HAL, which can assist hip and knee joint motion, might improve gait function for myelopathy [ 10 ], cerebral infarction [ 11 ], and cerebral palsy [ 12 ]. The single-joint type HAL can assist knee and elbow joint motion.…”
Section: Introductionmentioning
confidence: 99%